Bridging the Gap: Collaborative Models Between Institutions and Local Communities - nur, Muhammad (Journal Ligundi of Community Service, 2025)
Background Educational inequalities persist in remote and marginalized communities due to the lack of inclusive, locally adapted, and sustainable models of collaboration between formal institutions and grassroots stakeholders. Conventional institutional programs often operate in isolation from community realities, resulting in limited impact, resistance, and disengagement. The absence of integrative, context-aware, and mutually beneficial frameworks continues to hinder educational advancement and community resilience. Purpose This study aims to develop a collaborative model that bridges the gap between educational institutions and local communities to support equitable access, cultural responsiveness, and shared ownership in education. By leveraging principles from community-based education, transformative pedagogy, and cross-sectoral cooperation, the research contributes to the discourse on sustainable educational partnerships aligned with SDG 4 (Quality Education) and SDG 17 (Partnerships for the Goals). Method Using a qualitative Participatory Action Research (PAR) approach, the study engaged both institutional actors (e.g., schools, universities, NGOs) and community members (e.g., parents, teachers, religious leaders) across several underserved areas. Data collection involved collaborative workshops, stakeholder interviews, and community mapping. The model was co-designed to reflect local needs, values, and power dynamics, integrating elements such as shared decision-making, resource co-management, and culturally sensitive learning modules. Results The findings revealed that collaborative models foster trust, relevance, and sustainability in educational initiatives. Communities experienced improved engagement, agency, and intergenerational learning outcomes. Institutions reported increased effectiveness, cultural adaptability, and grassroots support. Notably, the model enabled decentralized leadership, diversified resource mobilization, and inclusive curriculum development. Conclusion This study presents a scalable and adaptive framework for bridging institutional and community divides in education. It emphasizes the significance of co-ownership, dialogue-based planning, and contextual pedagogy. The proposed model offers a strategic pathway for stakeholders aiming to build resilient, inclusive, and community-centered education systems in low-resource settings.